Renal leiomyosarcoma with intraperitoneal invasion through the mesocolon - Praderi, Raúl; Pardie, J (Cirugía del Uruguay, 2020)
The paper presents the results of the observation of a leiomiosarcoma of the left kidney in a 41-year-old patient with multiple neurofibromatosis. The tumor, of very large size, grew through the avascular area of the left mesocolon without infiltrating it, forming a thick intraperitoneal lobulation shaped like an hourglass.